REHABILITATION OF STROKE PATIENTS TREATED AT A COMMUNITY BASED REHABILITATION CENTRE - Rhoda, Anthea (Journal of Community and Health Sciences, 2020)
Aim: The overall aim of the study was to compile a profile of stroke patients receiving out-patient rehabilitation in the community. Included in the profile was the referral and rehabilitation process. Method: The study design was descriptive, utilizing a retrospective survey of patient documentation. Patient records were used to collate the data. Results: Records of 168 patients were included in the study. A large percentage (55.9%) of the patients were referred by primary level sources. Thirty three percent of the patients were assessed within their first two weeks post-stroke. Sixty nine percent of the patients received rehabilitation for less than 3 months with an average of one treatment session per week. Results indicate an improvement in functional status of the patients when comparing admission and discharge scores (p=< 0.0005). Conclusion: Out-patient community based rehabil itation could have a positive effect on the functional status of stroke patients.